Selección de semillas por los agricultores del Proyecto AgroClimas - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
This study was supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), within the framework of the project "Agroclimatic services and food safety information for better decision-making - AgroClimas" (Http://bit.ly/AgroClimas), led by the International Center for Tropical Agriculture (CIAT).